Changes in phosphatidylinositol 3-kinase 55 kDa gamma expression and subcellular localization may be caspase 6 dependent in paraquat-induced SH-SY5Y apoptosis. (July 2014) - Zhou, Y; Li, F; Tian, X; Wang, B; Ding, M; Pang, H
The neurotoxin paraquat (PQ) causes apoptosis of dopaminergic neurons in mammalian cell culture and animal models, mimicking an important pathological feature of Parkinson's disease (PD). The phosphoinositide 3-kinase (PI3K)/Akt pathway is critical for several major survival signals in central nervous system neurons. Phosphatidylinositol 3-kinase 55 kDa gamma ( p55PIK ) is a regulatory subunit of PI3Ks with important roles in cell proliferation, antiapoptosis, and cell cycle progression. However, p55PIK involvement in mechanisms regarding progression and maintenance of neurodegenerative diseases is largely undetermined. We used PQ-induced apoptosis in human dopaminergic SH-SY5Y cells to investigate the association between p55PIK expression levels, subcellular location, and apoptosis. p55PIK expression was reduced in SH-SY5Y cells and p55PIK messenger RNA and protein expression levels were decreased after PQ treatment. Apoptosis induced by PQ was associated with caspase activation and decreased p55PIK expression. Restoration of p55PIK expression was observed after coincubation with a caspase inhibitor. Overexpressed full-length p55PIK in SH-SY5Y and human embryonic kidney 293 cells showed specific distribution in the nucleus and was cleaved in vitro by recombinant caspase 6 (C6), but not C3 and C7. A p55PIK construct lacking 24 N -terminal amino acids (N24) was tested for the presence of a potential C6-recognizable sequence and was found to express its proteins outside the nucleus. The results suggest that p55PIK may be involved in PQ-induced apoptosis signal transduction and that N24 is crucial for p55PIK subcellular localization. Thus, p55PIK could be a substrate of activated C6 during apoptosis, leading to loss of original biological functions and redistribution to disturb cell cycle progression.